Consideration of Climate Change from a Global Bioethics Perspective (Revista Iberoamericana de Bioética, 2020)
This article discusses climate change in the context of global bioethics, which allows us to confront the human being with its discourse and its contradictions. It has created an otherness that it combats with a duality of behaviour, instituting law actions when they are unlawful. In Stockholm in 1972 a call was made to reduce activities that compromise the existence of life on the planet, including pollution. It did not decrease, however, and has increased with climate change, providing further evidence of the ambiguity of human thought. The genesis of this problem lies with the human being having become a biological element that threatens planetary security.
Keywords: climate change; global bioethics; bioethics